Design of temperature measuring circuit of S-type thermocouple based on temperature sensor - Wang Lequn; Wen Feng; Zhang Kaihua (Dianzi Jishu Yingyong)
Aiming at the problem that the traditional multi-channel S-type thermocouple temperature measurement system has low measurement accuracy and each channel is quite different, a high-precision S-type thermocouple temperature measurement system based on FPGA is proposed.The system uses FPGA as controller, with modular design, and uses AD590 to perform cold junction compensation for S-type thermocouples.A high-precision ADC is used to convert the collected temperature analog signal into a digital signal and transmit it to the upper computer for display and locates the temperature value through the look-up table method to improve the temperature measurement accuracy.After many tests, it is verified that the temperature acquisition accuracy of this temperature measurement circuit is better than 0.2%F.S. At present, the circuit design has been applied to engineering practice, which provides an effective and reliable means for the design of temperature measuring circuit of S-type thermocouple.